Future under sea ice light availability and algal bloom timing from CMIP6 model simulations - Heorton, Harold DBS.; Stroeve, Julienne C.; Veyssière, Gaëlle (Frontiers in Marine Science, 2025)
Arctic sea ice is projected to thin and reduce in extent significantly over the next century. Both sea ice and its overlying snow limit the amount of light that reaches the upper ocean, impacting the phenology of ocean primary productivity. Recent studies using in-situ data and pan-Arctic satellite observations emphasize the influence of current trends in sea ice and snow on the timing of under-ice, or ice residing algal blooms. This analysis is extended here using Climate Model Intercomparison Project (CMIP6) simulations to estimate future changes in under-ice light levels and to explore the driving factors. Under the SSP5-8.5 scenario, CMIP6 models project a significant reduction in sea-ice and snow thickness, causing light thresholds for algal blooms to be reached up to 60 days earlier by 2100 for regions such as the Chukchi Sea at higher latitudes. Areas such as the Labrador Sea at lower latitudes have limited changes due to relatively thinner sea ice and snow thicknesses. While this trend varies spatially and across models, snow thickness is a critical factor in high-latitude regions.